The greater the number of wins the greater the peak torque levels of shoulder internal rotators power of dominant hand in amateur boxing athletes - Tasiopoulos, I.; Tripolitsioti, A.; Dimitrios, S.; Pantelis, N. (Biology of Exercise, 2015)
The authors of this study concluded that the greater the number of wins, the greater the peak torque levels of shoulder internal rotators power of dominant hand in amateur boxing.